The SANU Memorandum, the Socialist Federativ Republic of Yugoslavia and Bosnia and Herzegovina (1986-1992) - Bećirović, Denis (Historical Thought, 2025)
In this paper the author focuses on the content and influence of the SANU Memorandum on the dissolution of the Socialist Federativ Republic of Yugoslavia and also the reflections of the dissolution of the Yugoslav state on events in Bosnia and Herzegovina.